The challenge of inclusive education in a Brazilian School: teachers’ concerns regarding inclusion (Research, Society and Development, 2016)
This intervention research analyzes the impact of implementation of the Brazilian inclusive education policy on the teachers of a public school. The intervention was based on Cultural-Historical Activity Theory, using the methodology of Change Laboratory. Such methodology is based on the idea of expansive learning, which proposes the collective creation of new solutions to deal with the contradictions faced in an activity system (in this case, the school). Inclusive education has been a challenge to this school and its teachers: most of them were dealing with it for the first time. Ten group sessions were carried out from March to December 2014 and data were collected during such sessions. Three categories emerged from the data in an attempt to explain the teachers’ concerns about inclusion: 1) inclusion as learning, 2) inclusion as fallacy and 3) manifestation of contradictions related to inclusion. Students’ effective learning was the least frequent category. Manifestation of contradictions was the main category, indicating that the proposed inclusive education must advance to improve students’ performance. Such advances could take place through facing the contradictions appointed by the subjects themselves. Under the light of the theoretical framework, it was possible to perceive that the contradictions reveal the tensions involved in the inclusion process and, at the same time, the potential for change they carry in themselves.